2019
DOI: 10.3390/f10050401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selected Factors on the Bending Deflection at the Limit of Proportionality and at the Modulus of Rupture in Laminated Veneer Lumber

Abstract: The deflection of a test material occurs under bending stress that is caused by force. In terms of plasticity and elasticity, the deflection can be quantified at two main areas, which are the limit of proportionality and the modulus of rupture. Both of these deflections are of great importance in terms of the scientific and practical use. These characteristics are particularly important when designing structural elements that are exposed to bending stress in terms of the size of the deflection in their practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Properties of lamellae and plywood used in furniture projects depend on many various factors, such as moisture content of veneers, temperature, pressure and pressing time [54][55][56][57][58]. Adhesive properties, its viscosity, thickness of adhesive layer, quality of adhesive application, mechanical properties of veneers, treatment quality or removal of small elements from the surface (saw dust) are other factors affecting the bending strength [59][60][61][62][63]. Due to high bending strength of lamellae during dynamic loading, laminated wood is preferred in furniture manufacturing, especially chairs and beds [64].…”
Section: Introductionmentioning
confidence: 99%
“…Properties of lamellae and plywood used in furniture projects depend on many various factors, such as moisture content of veneers, temperature, pressure and pressing time [54][55][56][57][58]. Adhesive properties, its viscosity, thickness of adhesive layer, quality of adhesive application, mechanical properties of veneers, treatment quality or removal of small elements from the surface (saw dust) are other factors affecting the bending strength [59][60][61][62][63]. Due to high bending strength of lamellae during dynamic loading, laminated wood is preferred in furniture manufacturing, especially chairs and beds [64].…”
Section: Introductionmentioning
confidence: 99%
“…Compliance coefficients in fibber direction or principal material coordinate system (Figure 6b) are: (16) Using Castigliano's theorem, the deflection of the cantilever end, at the load P can be calculated with: (17) 2.4 Cantilever deflection using FEM 2.4. Otklon konzole dobiven metodom konačnih elemenata Numerical analysis is performed using commercial software SolidWorks 2020 and its Simulation module based on the finite element method (FEM).…”
Section: Deflection Of Half-circle Cantilever 232 Otklon Polukružne K...mentioning
confidence: 99%
“…A study (Merhar, 2020) had shown that the laminate theory, which was well established and applied in the world of synthetic composites, could also be applied to plywood composites. The influence of fibre reinforcement and wood species on the physical and mechanical properties of veneer plywood as well as on laminated veneer lumber was also investigated (Brezović et al, 2003;Bal, 2014;Sikora et al, 2019). The CLPT and the finite element method (FEM) were used in a study (Makowski, 2019) to determine stress distribution in individual layers of 18 mm thick beech plywood, in the 3-point flexural bending test.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…Kallakas et al [3] investigated the influence of different layer structures and the use of various wood species on the mechanical properties of plywood, while Biadala et al [4] carried out similar research trying to develop water-resistant plywood with combinations of different wood species. The influence of fibre reinforcement and wood species on the physical and mechanical properties of veneer plywood as well as on laminated veneer lumber was also investigated [5][6][7], as well as the influence of veneer densification on the mechanical properties of plywood [8]. Surface layer polymerisation by active monomers proved to have a positive effect on the modulus of elasticity and strength of wood-based flooring panels [9].…”
Section: Introductionmentioning
confidence: 99%